Perubahan Budaya Kerja Pasca-Pandemi COVID-19 - Elisa Sah Putri; Widia Dhari (Jurnal Manajemen Bisnis Era Digital, 2025)
The COVID-19 pandemic has served as a major catalyst in transforming work patterns and organizational culture across various sectors. This study aims to provide an in-depth description of changes in work culture after the pandemic using a qualitative descriptive method. Data were collected through literature reviews from scientific journals, books, and relevant research reports. The results show that the pandemic triggered significant transformations in organizational work systems, particularly through the adoption of flexible work models such as work from home (WFH) and hybrid working. This shift was accompanied by an increased reliance on digital technology as the primary tool for coordination, communication, and performance evaluation. In addition to systemic changes, the pandemic fostered new organizational values such as flexibility, empathy, trust, and work-life balance. Human-centered leadership has become increasingly vital for maintaining employee motivation and psychological well-being. In the context of human resource management, recruitment, training, and performance evaluation have become more result-oriented, emphasizing actual contributions rather than physical presence.